Motor and Nonmotor Symptoms of Parkinson's Disease: Antagonistic Pleiotropy Phenomena Derived from α-Synuclein Evolvability?. (22nd November 2018) - Takamatsu, Yoshiki; Fujita, Masayo; Ho, Gilbert J.; Wada, Ryoko; Sugama, Shuei; Takenouchi, Takato; Waragai, Masaaki; Masliah, Eliezer; Hashimoto, Makoto
Abstract : Lewy body diseases, such as Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA), are associated with a wide range of nonmotor symptoms (NMS), including cognitive impairment, depression and anxiety, sleep disorders, gastrointestinal symptoms, and autonomic failure. The reason why such diverse and disabling NMS have not been weeded out but have persisted across evolution is unknown. As such, one possibility would be that the NMS might be somehow beneficial during development and/or reproductive stages, a possibility consistent with our recent view as to the evolvability of amyloidogenic proteins (APs) such as α -synuclein ( α S) and amyloid- β (A β ) in the brain. Based on the heterogeneity of protofibrillar AP forms in terms of structure and cytotoxicity, we recently proposed that APs might act as vehicles to deliver information regarding diverse internal and environmental stressors. Also, we defined evolvability to be an epigenetic phenomenon whereby APs are transgenerationally transmitted from parents to offspring to cope with future brain stressors in the offspring, likely benefitting the offspring. In this context, the main objective is to discuss whether NMS might be relevant to evolvability. According to this view, information regarding NMS may be transgenerationally transmitted by heterogeneous APs to offspring, preventing or attenuating the stresses related to such symptoms. On the other hand, NMS associated with Lewy body pathology might manifest through an aging-associated antagonistic pleiotropy mechanism. Given that NMS are not only specific to Lewy body diseases but also displayed in other disorders, including amyotrophic lateral sclerosis (ALS) and Huntington's disease (HD), these conditions might share common mechanisms related to evolvability. This might give insight into novel therapy strategies based on antagonistic pleiotropy rather than on individual NMS from which to develop disease-modifying therapies.